Wakefields excitation in plasma, produced by a sequence of electron bunches in neutral gas, accelerating and focusing electrons by them - Kiselev, V.A.; Linnik, A.F.; Onishchenko, I.N.; Pristupa, V.I. (Вопросы атомной науки и техники, 2011)
Experiments on wakefield excitation by a long sequence of relativistic electron bunches in plasma, formed by head
bunches of the same sequence in neutral gas of various pressure are presented. The ranges of pressure are found, in
which beam-plasma discharge is developed, that leads to intensification of plasma generation. Acceleration and
focusing of bunches electrons that is determined by ratio of the bunch length to its diameter and detuning between
bunches repetition frequency and wakefield frequency, are investigated. Представлено експерименти по збудженню кільватерних полів довгою послідовністю релятивістських
електронних згустків у плазмі, яка створена головними згустками тієї ж послідовності в нейтральному газі
різного тиску. Знайдено області тиску газу, в яких розвивається пучково-плазмовий розряд, що приводить до
інтенсифікації генерації плазми. Досліджені прискорення та фокусировка електронів згустків, які визначаються
відношенням довжини згустку до його діаметру і розстройкою між частотою слідування згустків і частотою
збуджуваного кільватерного поля. Представлены эксперименты по возбуждению кильватерных полей длинной последовательностью
релятивистских электронных сгустков в плазме, образуемой головными сгустками этой же последовательности
в нейтральном газе различного давления. Найдены области давлений газа, в которых развивается пучково-
плазменный разряд, приводящий к интенсификации генерации плазмы. Исследованы ускорение и фокусировка
электронов сгустков, определяемые отношением длины сгустка к его диаметру и расстройкой между частотой
следования сгустков и частотой возбуждаемого кильватерного поля.